The Meaning of Breast Cancer Risk for African American Women - Phillips, Janice (2011)
PURPOSE: To describe African American women’s experience of being at high risk for breast cancer. DESIGN: A hermeneutic phenomenological approach was used to guide in-depth interviews and analysis. Methods to ensure trustworthiness and rigor were included. METHODS: Open interviews were conducted with 20 African American women who were at high risk for breast cancer (family history, personal history, genetic mutation). They were recruited from a cancer risk clinic and community based settings. Data were transcribed verbatim and themes were labeled among and between all interviews. FINDINGS: Five themes were identified: (a) life changing experience; (b) relationships: fears, support, and concerns; (c) the health care experience; (d) raising awareness; and (e) strong faith. CONCLUSIONS: Young women at high risk for breast cancer have unique emotional and support needs that are shaped by stage in life, relationships with significant others, their faith, and interactions with the health care delivery system.